PERUBAHAN INTENSITAS GATAL DAN INDEKS KUALITAS HIDUP DERMATOLOGI (DLQI) SETELAH INTERVENSI MINYAK KLENTIK DI PANTI SASANA TRESNA WERDHA RIA PEMBANGUNAN CIBUBUR - Sukmawati Tansil Tan; Yohanes Firmansyah; Edwin Destra; Jessica Elizabeth; Yana Sylvana; Noer Saelan Tadjudin (Yayasan Pendidikan Medika Indonesia, 2022)
Population Reference Bureau estimates that by 2030 Indonesia will experience an increase in population to 365,3 million. This condition will cause an increase in health problems in the elderly population. Elderly health problems that often occur especially in the skin are dryness and pruritus/ itchiness caused by decreased levels of skin hydration with increasing age, which will further affect the elderly quality of life. One way to cope with the complaints of skin dryness and itchiness is to provide skin moisturizer. Skin moisturizers that are developing at this time are made from virgin olive oil and virgin coconut oil which, when combined together is commonly known as klentik oil. The Dermatology Life Quality Index questionnaire is a holistic measure of quality of life that is commonly used to measure quality of life in skin diseases. This study aims to determine changes in the quality of life of the elderly after providing interventions in the form of klentik oil and determine the effectiveness of klentik oil in reducing elderly skin itchiness. In this study, respondents were given klentik oil which applied to both arms 15 minutes after bathing. Dermatology Life Quality Index was measured twice, before the respondent was given the intervention and on the 21st day. This study showed that klentik oil can reduce the intensity of itchiness and improve the elderly quality of life measured by Dermatology Life Quality Index questionaire.